(untitled) (Balneo and PRM Research Journal, 2024)
Adrenal incidentalomas (AIs) are clinically silent adrenal masses that are unintentionally found during various abdominal imaging procedures. Our objective was to evaluate the bone profile in menopausal females diagnosed with AI versus a non-AI control group. This was an observational, retrospective, multi-centric, case-control study, a sub-analysis of PRECES study (“Parameters of Romanian Patients with Endocrine Conditions with or without Endocrine Surgery: real-world-evidence and retrospective study”), a multi-centric, Romanian collaborative in the field of endocrinology and connected specialities (real-world community setting). Inclusion criteria: women in menopause between 40 and 85 years. Ex-clusion criteria: active endocrine tumours or cancers, prior or current medication against osteoporosis. Assessments included bone turnover markers, central DXA, FRAX-based os-teoporotic fracture risk evaluation. AIs were defined as having a value of second day plas-ma morning cortisol after 1-mg dexamethasone suppression test of < 1.8 µg/dL [without mild autonomous cortisol secretion (MACS free), as seen in control group that did not dis-play the imaging evidence of an adrenal tumour] or between 1.8 and 5 µg/dL (MACS sub-group). Results: Demographic features of both groups (N=39 versus 95 patients) were simi-lar in terms of age (60.95±10.46 versus 61.55±7.2 years), years since menopause (14.92±10.32 versus 14.52±8.85 years), body mass index (28.03 versus 27 kg/sqcm); (p>0.1 for each). Osteopenia was the most prevalent DXA category in each group (43.6% versus 53.7%), followed by osteoporosis (20.5% versus 22.1%), while lumbar, total hip, femoral neck BMD were similar between AIs and controls. A statistically significant lower osteocal-cin in subjects with AIs, with a median (Q1, Q3) of 16.5 (11.96-20.09) ng/mL compared with the value in control groups of 23.17 (15.9-31.46) ng/mL (p=0.003) was found. In AIs group, serum baseline morning cortisol positively correlated with lumbar Z-score, and correlation coefficient reached a statistical significance (p = 0.035). Of note, a tendency for correlation with total hip BMD was found, too. To conclude, decreased osteocalcin might be the signa-ture of mild cortisol anomalies in AIs, but DXA-BMD and FRAX algorithm revealed similar parameters in AI group versus controls, as found between MACS and MACS free sub-groups.